Metabolic score for insulin resistance and the incidence of cardiovascular disease: a meta-analysis of cohort studies - He, Ye; He, Jiading; Chen, Dongping; Xiao, Jianmin (Frontiers in Endocrinology, 2025)
Cardiovascular disease (CVD) remains the leading global cause of mortality, with insulin resistance as a pivotal metabolic risk factor that promotes endothelial dysfunction, inflammation, and atherosclerosis via mechanisms such as impaired nitric oxide signaling and enhanced oxidative stress. The metabolic score for insulin resistance (METS-IR), a non-insulin-based index derived from fasting blood glucose, triglycerides, high-density lipoprotein cholesterol, and body mass index, offers a practical surrogate for assessing insulin sensitivity. However, its association with incident CVD has not been systematically evaluated in a meta-analysis. This meta-analysis aimed to quantify the relationship between baseline METS-IR and the incidence of composite CVD, coronary artery disease (CAD), and stroke in adults without baseline CVD, including categorical, continuous, and dose-response analyses. We searched PubMed, EMBASE, Cochrane Library, and Web of Science up to August 2, 2025, for cohort studies. Hazard ratios (HRs) were pooled using random-effects models to account for heterogeneity for highest versus lowest METS-IR categories and per standard deviation (SD) increment. Nonlinear dose-response relationships were modeled with restricted cubic splines. Heterogeneity, sensitivity, and publication bias were assessed. Eight cohort studies involving 437,283 participants were included. Highest vs. lowest METS-IR was associated with increased risks (HR [95% CI]; I²): composite CVD (1.65 [1.36-2.02]; 85.6%), CAD (1.82 [1.50-2.20]; 59.7%), stroke (1.47 [1.19-1.83]; 76.3%). Per SD increment: composite CVD (1.16 [1.10-1.22]; 70.7%), CAD (1.18 [1.11-1.25]; 52.4%), stroke (1.13 [1.06-1.19]; 67.9%). Dose-response analyses revealed a nonlinear association for CAD (P for nonlinearity: 0.011), marginal nonlinearity for stroke (P: 0.072), and suggested nonlinearity for composite CVD (P: 0.145), with inflection points at METS-IR values of 40.56 (composite CVD), 38.24 (CAD), and 48.88 (stroke), beyond which risks appeared to accelerate. Elevated METS-IR independently predicts higher incidence of composite CVD, CAD, and stroke with nonlinear thresholds for CAD, marginal nonlinear thresholds for stroke, and potential nonlinear thresholds for composite CVD, despite moderate-to-high heterogeneity, supporting its integration into risk stratification and preventive strategies for metabolic health management.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?ID=CRD420251104293, identifier CRD420251104293.